Electrolyte, electrochemical device and electronic device
By using electrolyte containing substances A, substance B and substance C in lithium-ion batteries, the problem of poor discharge performance of lithium-ion batteries under floating charging and low temperature conditions is solved, and better capacity retention and thickness expansion are achieved rate and high rate discharge performance.
Patent Information
- Application Number
- CN202411605003.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing lithium-ion batteries have poor discharge performance under special conditions such as floating charging and low temperature, making it difficult to maintain good discharge performance.
An electrolyte containing substance A, substance B and substance C is used, substance A includes 1-propylene-1,3-sulfonate lactone and/or tripropynyl phosphate, substance B includes vinylene carbonate and/or Dimethyl sulfone, substance C includes a series of dimethyl imidazole phosphate derivatives. The electrolyte synergistically forms a uniform and dense solid electrolyte interface mask, improving the stability and discharge performance of the battery.
The capacity retention rate and thickness expansion rate of lithium-ion batteries under floating charging conditions are improved, and the high-rate discharge performance at low temperatures is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art
[0002] With the rapid development of lithium-ion batteries, the diversification of application scenarios has put forward higher requirements for the design and use of lithium-ion batteries, especially requiring that the battery can also have excellent discharge capacity under some special conditions. Therefore, there is an urgent need for a battery that can maintain good discharge performance under special conditions such as floating charge and low temperature. Summary of the invention
[0003] In view of this, the present application provides an electrolyte, an electrochemical device and an electronic device, which can improve the floating charge capacity retention rate, reduce the floating charge thickness expansion rate, and at the same time improve the low-temperature high-rate discharge performance.
[0004] In the first aspect, the embodiment of the present application provides an electrolyte, the electrolyte comprising substance A, substance B and substance C. Wherein, substance A comprises 1-propylene-1,3-sultone and / or tripropynyl phosphate, substance B comprises vinylene carbonate and / or dimethyl sulfone, and substance C comprises at least one of 1-dodecyl-3-methyl-imidazole dimethyl phosphate, 1-tetradecyl-3-methyl-imidazole dimethyl phosphate, 1-hexadecyl-3-methyl-imidazole dimethyl phosphate, 1-octadecyl-3-methyl-imidazole dimethyl phosphate, 1-dodecyl-3-methyl-imidazole diethyl phosphate or 1,3-dimethylimidazole dimethyl phosphate. Based on the total mass of the electrolyte, the mass percentage of substance A is a%, the mass percentage of substance B is b%, and the mass percentage of substance C is c%, 0.1≤b / a≤50, 0.2≤a≤2.5, 1.2≤b≤6.4, and 1.5≤c≤4.
[0005] Based on the electrolyte of the embodiments of the present application, the inventors found that when the electrolyte contains the above-mentioned types of substance A, substance B and substance C, there is a synergistic effect between substance A, substance B and substance C, which can improve the overall stability of the battery system. It was observed through atomic force microscopy that a more uniform and dense solid electrolyte interface film can be formed on the interface of the positive electrode lithium cobalt oxide material than when no substance A, substance B and substance C are added, thereby improving the floating capacity retention rate of the electrochemical device; at the same time, substance C can participate in the formation process of the CEI film and firmly adhere to the surface of the positive electrode lithium cobalt oxide material, reduce the oxidation decomposition reaction of the positive electrode material and the electrolyte, thereby maintaining the stability of the surface of the positive electrode material and the structural compressive resistance, reducing the floating thickness expansion rate of the electrochemical device, and promoting the back and forth insertion and extraction of lithium ions at low temperatures, reducing lithium precipitation at the interface, and improving high-rate discharge performance.
[0006] In some embodiments, the electrolyte satisfies at least one of the following conditions: (1) 2≤b / a≤4; (2) 0.7≤a≤1.6. By adjusting the contents of substance A and substance B, and the content ratio of substance B to substance A within the above range, the range of the two substances can be limited to a more appropriate content, thereby further improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, it can better promote the back and forth insertion and extraction of lithium ions at low temperatures, thereby reducing lithium precipitation at the interface and further improving the high rate discharge performance.
[0007] In some embodiments, 2.2≤a+c≤4.7. By limiting the mass percentage of substance C and the sum of its content with substance A within a suitable range, substance C can participate in the formation process of the CEI film and firmly adhere to the surface of the positive electrode lithium cobalt oxide material, reduce the oxidation decomposition reaction of the positive electrode material and the electrolyte, thereby maintaining the surface stability and structural compressive resistance of the positive electrode material, thereby further improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, it can better promote the back and forth insertion and extraction of lithium ions at low temperatures, thereby reducing lithium precipitation at the interface and further improving the high-rate discharge performance.
[0008] In some embodiments, the electrolyte further includes substance D, and substance D includes 1-propyl phosphoric acid cyclic anhydride. Based on the total mass of the electrolyte, the mass percentage of substance D is d%, 0.1≤d≤2, 0.8≤a+d≤3.4. By adding 1-propyl phosphoric acid cyclic anhydride, and limiting the content of substance D and the sum of the contents of substance D and substance A within the above range, 1-propyl phosphoric acid cyclic anhydride can form a better synergistic effect with substance A, thereby improving the test pass rate of the battery in the puncture test and the battery, and can effectively inhibit the self-discharge behavior of the battery in a high temperature environment, thereby improving the storage performance of the battery under high temperature conditions and the capacity retention rate and capacity recovery rate at high temperature.
[0009] In some embodiments, the electrolyte further includes a fluorine-containing substance F, and the fluorine-containing substance F includes lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide. Based on the total mass of the electrolyte, the mass percentage of the fluorine-containing substance F is f%, 0.3≤f≤2, 0.7≤a+f≤2.7. By adding a certain amount of lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide, and limiting the total content of them and substance A within a reasonable range, it can appropriately play a role in lithium supplementation, so that the lithium-cobalt ratio on the material meets a suitable range, so that the lithium ions consumed in the first cycle will not affect the subsequent charging and discharging, and to a certain extent, it can also improve the storage performance of the battery at high temperature.
[0010] In some of the embodiments, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate in the fluorine-containing substance F is f1%, 0.3≤f1≤1.5. By controlling the content of lithium difluorophosphate in the fluorine-containing substance F within the above range, it can help form a more stable CEI film under high temperature conditions, slow down the self-discharge rate of the battery in a high temperature environment, and thus further improve the storage performance of the battery at high temperature and the test pass rate in the needle test.
[0011] In a second aspect, an embodiment of the present application provides an electrochemical device, comprising an isolation membrane and the above-mentioned electrolyte.
[0012] In some of the embodiments, the separator in the electrochemical device includes a porous membrane, and the pore size distribution coefficient of the porous membrane is 1.5 to 4.5. When the pore size distribution coefficient of the porous membrane in the embodiment of the present application meets this range, it can be beneficial for the pore size on the separator to meet a suitable range, thereby improving the extension ability of the separator in the lateral and longitudinal directions, and improving the overall structural stability of the separator. The separator will also have a more excellent compressive resistance under the abuse test, so that the secondary battery prepared has a higher test pass rate in the side extrusion test, and at the same time improves the high temperature performance to a certain extent.
[0013] In some of the embodiments, the porous membrane of the separator includes inorganic particles and a binder, and the aspect ratio of the inorganic particles is 1 to 5. When the aspect ratio of the inorganic particles is limited to meet the scope of the present application, the pore size on the separator can be made to meet a suitable range, the mechanical strength and surface hardness of the separator can be improved, and the extension ability of the separator in the transverse and longitudinal directions can be maintained within a suitable gap range. The separator will also have a more excellent compressive resistance in the abuse test, and the secondary battery prepared has a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0014] In some embodiments, the pore size in the isolation membrane satisfies at least one of the following conditions:
[0015] (a) The pores with a pore size of 0.0375 μm on the isolation membrane account for 26% to 38% of the total pores;
[0016] (b) The pores with a pore size of 0.0325 μm on the isolation membrane account for 42%~58% of the total pores.
[0017] When the pore size on the isolation membrane meets the range specified in this application, the overall mechanical strength of the isolation membrane is higher, and the isolation membrane will also have better compressive resistance in the abuse test. Therefore, the secondary battery produced has a higher test pass rate in the side extrusion test, and at the same time improves the high temperature performance to a certain extent.
[0018] In some of the embodiments, the circularity of the pore size in the cross section of the porous membrane in the separator meets the range of 0.6 to 0.72. When the circularity of the pore size in the cross section of the porous membrane in the separator meets the range of the present application, the pores in the separator are in a suitable range and are not too large or too small, the overall mechanical strength of the separator is higher, the separator will also have a better compressive resistance in the abuse test, the secondary battery prepared has a higher test pass rate in the side extrusion test, and the high temperature performance is improved to a certain extent.
[0019] In some of the embodiments, the difference between the elongation of the porous film in the separator at 65°C in the MD direction and the TD direction is 35% to 80%. The MD direction is the mechanical direction, the longitudinal direction. The TD direction is perpendicular to the mechanical direction, that is, the transverse direction. When the difference between the elongation in the MD and TD directions of the separator meets the scope of this application, the separator as a whole can have a relatively uniform tensile strength, improve the structural stability of the separator under external pressure, and make the secondary battery prepared have a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0020] In some of the embodiments, the thickness variation of the porous membrane in the width direction is 0.2 μm to 0.7 μm. When the thickness variation of the porous membrane in the width direction is limited to meet the requirements of the present application, the compressive strength of the isolation membrane can be effectively improved, so that the isolation membrane has a higher test pass rate in the side extrusion test, and the high temperature performance can be improved to a certain extent.
[0021] In a third aspect, an embodiment of the present application provides an electronic device, comprising the above-mentioned electrochemical device.
[0022] During the charge and discharge process of the battery, there is a synergistic effect between the substances A, B and C in the electrolyte of the present application, which can improve the overall stability of the battery system. It is observed through atomic force microscopy that a more uniform and dense solid electrolyte interface film can be formed on the interface of the positive electrode lithium cobalt oxide material compared to when no substances A, B and C are added. The stable interface film is conducive to improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, the electrolyte can promote the back and forth insertion and extraction of lithium ions in the battery at low temperatures, thereby reducing lithium precipitation at the interface and improving high-rate discharge performance.
[0023] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0024] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application. As used in the present application, the terms "include", "contain" and "comprise" are used with their open, non-restrictive meanings.
[0025] In addition, sometimes amounts, ratios and other numerical values are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.
[0026] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0027] Electrolyte
[0028] The first aspect of the embodiment of the present application provides an electrolyte, the electrolyte includes substance A, substance B and substance C, substance A includes 1-propylene-1,3-sultone and / or tripropynyl phosphate. Substance B includes vinylene carbonate and / or dimethyl sulfone. Substance C includes at least one of 1-dodecyl-3-methyl-imidazole dimethyl phosphate, 1-tetradecyl-3-methyl-imidazole dimethyl phosphate, 1-hexadecyl-3-methyl-imidazole dimethyl phosphate, 1-octadecyl-3-methyl-imidazole dimethyl phosphate, 1-dodecyl-3-methyl-imidazole diethyl phosphate or 1,3-dimethylimidazole dimethyl phosphate. When the electrolyte contains the above-mentioned types of substances A, substance B and substance C, the inventors found that the synergistic effect of their presence can improve the overall stability of the battery system. Specifically, when the above-mentioned substances A, B and C contained in the electrolyte can synergistically promote the reaction between the positive electrode material and the electrolyte at the solid-liquid interface, the solid electrolyte interface film covering the interface of the positive electrode lithium cobalt oxide material is more uniform and dense, thereby improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, it can promote the back and forth insertion and extraction of lithium ions at low temperatures, thereby reducing lithium precipitation at the interface and improving high-rate discharge performance.
[0029] In some embodiments, based on the total mass of the electrolyte, the mass percentage of substance A is a%, the mass percentage of substance B is b%, 0.1≤b / a≤50, 0.2≤a≤2.5, 1.2≤b≤6.4. Exemplarily, the value of the content ratio b / a of substance B to substance A can be 0.1, 0.2, 0.5, 0.6, 1.0, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 20.0, 40.0, 50.0 or a range consisting of any two of these values. Exemplarily, the value of the mass percentage a of substance A can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.5 or a range consisting of any two of these values. Exemplarily, the value of the mass percentage b of substance B can be 1.2, 1.4, 1.6, 2.0, 2.2, 2.5, 3.0, 4.0, 5.0, 5.8, 6.4 or a range consisting of any two of these values. By further limiting the ratio of substance B to substance A, and the content of substance A and substance B to meet the scope of this application, the range of the two substances can be limited to a suitable content, thereby further improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, it can better promote the back and forth insertion and extraction of lithium ions at low temperatures, thereby reducing lithium precipitation at the interface and improving high rate discharge performance.
[0030] In some embodiments, in some embodiments, based on the total mass of the electrolyte, the mass percentage content of substance C is c%, 1.5≤c≤4, 2.2≤a+c≤4.7. Exemplarily, the mass percentage content c of substance C can be 1.5, 2.0, 2.5, 3.0, 3.5, 4.0 or a range consisting of any two of these values. The value of the sum of the mass percentage content c% of substance C and the mass percentage content a% of substance A a+c can be 2.2, 2.5, 3.0, 3.5, 4.0, 4.7 or a range consisting of any two of these values. By introducing substance C in the present application and limiting the sum of its content and the content of substance A within a suitable range, substance C can be firmly attached to the surface of the positive electrode lithium cobalt oxide material by participating in the formation process of the CEI film, reducing the oxidation decomposition reaction of the positive electrode material and the electrolyte, thereby maintaining the stability of the surface of the positive electrode material and the structural compressive resistance, thereby further improving the floating capacity retention rate of the electrochemical device and reducing the floating thickness expansion rate of the electrochemical device. At the same time, it can better promote the back-and-forth insertion and extraction of lithium ions at low temperatures, thereby reducing lithium plating at the interface and further improving high-rate discharge performance.
[0031] In some embodiments, the electrolyte further includes substance D, substance D includes 1-propylphosphoric acid cyclic anhydride, and based on the total mass of the electrolyte, the mass percentage content of substance D is d%, 0.1≤d≤2, 0.8≤a+d≤3.4. Exemplarily, the value of the mass percentage content d of substance D can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0 or a range consisting of any two of these values. Exemplarily, the value of the sum of the mass percentage content d% of substance D and the mass percentage content a% of substance A a+d can be 0.8, 2.0, 2.5, 3.0, 3.4 or a range consisting of any two of these values. By adding 1-propyl phosphoric acid cyclic anhydride and limiting the content of 1-propyl phosphoric acid cyclic anhydride and the sum of the contents of 1-propyl phosphoric acid cyclic anhydride and substance A within the above range, 1-propyl phosphoric acid cyclic anhydride and substance A can form a better synergistic effect, thereby improving the test pass rate of the battery in the puncture test and the battery, and can effectively inhibit the self-discharge behavior of the battery in a high temperature environment, thereby improving the storage performance of the battery under high temperature conditions.
[0032] In some embodiments, the electrolyte further includes a fluorine-containing substance F, and the fluorine-containing substance F includes lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide. Based on the total mass of the electrolyte, the mass percentage content of the fluorine-containing substance F is f%, 0.3≤f≤2, 0.7≤a+f≤2.7. Exemplarily, the value of the mass percentage content f of the fluorine-containing substance F can be 0.3, 0.5, 0.7, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0 or a range consisting of any two of these values. Exemplarily, the value of the sum a+f of the mass percentage content f% of the fluorine-containing substance F and the mass percentage content a% of substance A can be 0.7, 1.0, 1.5, 1.8, 2.0, 2.5, 2.7 or a range consisting of any two of these values. By adding a certain amount of lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide and limiting the total content of them and substance A within a reasonable range, it is possible to properly supplement lithium so that the lithium-to-cobalt ratio on the material meets a suitable range. On the basis of properly supplementing lithium ions, it is possible to avoid excessive lithium ions occupying the cobalt sites, so that the lithium ions consumed in the first cycle will not affect the subsequent charge and discharge. Therefore, the structural stability of the positive electrode material can be improved, and to a certain extent, the storage performance of the battery at high temperatures can also be improved.
[0033] In some embodiments, based on the total mass of the electrolyte, the mass percentage of lithium difluorophosphate in the fluorine-containing substance F is f1%, 0.3≤f1≤1.5. Exemplarily, the mass percentage of lithium difluorophosphate f1 can be 0.3, 0.5, 0.7, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or a range consisting of any two of these values. By controlling the content of lithium difluorophosphate within the above range, it can help form a CEI film that is more stable under high temperature conditions and slow down the self-discharge rate of the battery in a high temperature environment, thereby further improving the storage performance of the battery at high temperature and the test pass rate in the puncture test.
[0034] In some embodiments, the electrolyte may further include vinyl sulfate, 4-methylethylene sulfate, 1,3-propane sultone, 1,4-butane sultone, succinonitrile, glutaronitrile, adiponitrile, 2-methyleneglutaronitrile, dipropylmalononitrile, 1,3,6-hexanetrinitrile, 1,2,6-hexanetrinitrile, 1,3,5-pentanetrinitrile or 1,2-bis(cyanoethoxy)ethane.
[0035] In some embodiments, the electrolyte may further include other ionizable lithium salts, including at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, and is preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less.
[0036] In some embodiments, the electrolyte also includes at least one of fluoroether, fluoroethylene carbonate or ether nitrile. In some embodiments, the electrolyte may also include a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorocarbonate compound or a combination thereof. Examples of linear carbonate compounds are ethyl propionate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate or a combination thereof.
[0037] Examples of cyclic carbonate compounds are ethylene carbonate, propylene carbonate, butylene carbonate, vinyl ethylene carbonate, or a combination thereof. Examples of fluorinated carbonate compounds are fluoroethylene carbonate, 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or a combination thereof.
[0038] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0039] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0040] Examples of other organic solvents are 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphoric acid esters, or combinations thereof.
[0041] Electrochemical Devices
[0042] The second aspect of the embodiment of the present application provides an electrochemical device, comprising a separator, an electrolyte, a positive electrode sheet and a negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and the electrolyte is any one of the above electrolytes.
[0043] In some embodiments, the isolation membrane includes a porous membrane, and the pore size distribution coefficient of the porous membrane is 1.5 to 4.5. For example, the pore size distribution coefficient of the porous membrane can be 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 or a range formed by any two of the values. When the pore size distribution coefficient of the porous membrane in the embodiment of the present application meets this range, it can be beneficial for the pore size on the isolation membrane to meet a suitable range, thereby improving the extension ability of the isolation membrane in the lateral and longitudinal directions, and improving the overall structural stability of the isolation membrane. The isolation membrane will also have a more excellent compressive resistance under the abuse test, so that the secondary battery has a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0044] In some embodiments, the porous film of the isolation membrane includes inorganic particles and a binder, and the aspect ratio of the inorganic particles is 1 to 5. For example, the aspect ratio of the inorganic particles can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or a range formed by any two of the values. When the aspect ratio of the inorganic particles is limited to meet the scope of the present application, the pore size on the isolation membrane can be made to meet a suitable range, the mechanical strength and surface hardness of the isolation membrane can be improved, and the extension ability of the isolation membrane in the lateral and longitudinal directions can be maintained in a suitable gap range. The isolation membrane will also have a more excellent compressive resistance in the abuse test, and the secondary battery prepared has a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0045] In some embodiments, the pore size in the isolation membrane satisfies at least one of the following conditions:
[0046] (a) the number of pores with a pore size of 0.0375 μm on the isolation membrane accounts for 26% to 38% of the total number of pores, for example, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38% or a range formed by any two of these values;
[0047] (b) The pores with a pore size of 0.0325 μm on the isolation membrane account for 42% to 58% of the total number of pores, for example, 42%, 45%, 47%, 49%, 51%, 53%, 55%, 57%, 58% or a range formed by any two of these values.
[0048] When the pore size on the isolation membrane meets the range specified in this application, the overall mechanical strength of the isolation membrane is higher, and the isolation membrane will also have better compressive resistance in the abuse test. The secondary battery produced has a higher test pass rate in the side extrusion test, and at the same time improves the high temperature performance to a certain extent.
[0049] In some of the embodiments, the thickness variation of the porous membrane in the width direction is 0.2 μm to 0.7 μm. For example, the thickness variation of the porous membrane in the width direction can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or a value within the range formed by any two of these values. When the thickness variation of the porous membrane in the width direction is limited to meet the requirements of this application, the thickness non-uniformity of the isolation membrane in the width direction can be effectively reduced, thereby improving the stability and compressive resistance of the overall structure of the isolation membrane, so that the isolation membrane has a higher test pass rate in the side extrusion test, and can improve the high temperature performance to a certain extent.
[0050] In some embodiments, the circularity of the pore size in the porous membrane cross section of the separator meets 0.6~0.72. For example, the aspect ratio of the circularity of the pore size in the porous membrane cross section of the separator can be 0.60, 0.61, 0.62, 0.63, 0.65, 0.67, 0.69, 0.70, 0.72 or a range formed by any two of the values. When the circularity of the pore size in the porous membrane cross section of the separator meets the scope of the present application, the pores in the separator are in a suitable range, not too large or too small, the overall mechanical strength of the separator is higher, and the separator will also have a more excellent compressive resistance in the abuse test, and the obtained secondary battery has a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0051] In some embodiments, the difference between the elongation of the porous membrane in the separator at 65°C in the MD direction and the TD direction is 35% to 80%. For example, the difference between the elongation in the MD direction and the TD direction can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any range therebetween. When the difference between the elongation in the MD and TD directions of the separator meets the scope of this application, the separator as a whole can have a relatively uniform tensile strength, improve the structural stability of the separator under external pressure, and make the secondary battery have a higher test pass rate in the side extrusion test, while improving the high temperature performance to a certain extent.
[0052] In some embodiments, the isolation film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film is in the range of about 3 μm to 500 μm.
[0053] In some embodiments, the surface of the isolation membrane may further include a porous layer, which is disposed on at least one surface of the isolation membrane, and the porous layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance, and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece.
[0054] In some embodiments, the positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer may be located on one side or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only, and other suitable thicknesses may be used.
[0055] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material is preferably lithium cobalt oxide as the positive electrode material, or may be at least one of lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated.
[0056] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.
[0057] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one side or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.
[0058] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.
[0059] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose, polyacrylic acid, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be made of any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.
[0060] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto. In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode sheet, a separator, and a negative electrode sheet are wound or stacked in sequence to form an electrode assembly, which is then placed in a housing such as an aluminum-plastic film for packaging, an electrolyte is injected, and the battery is formed and packaged to form a lithium-ion battery.
[0061] Electronic Devices
[0062] The third aspect of the embodiment of the present application provides an electronic device, including any of the above-mentioned electrochemical devices. The electronic device of the embodiment of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0063] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.
[0064] Preparation of lithium-ion batteries
[0065] Positive electrode sheet: Mix the positive electrode active materials of lithium cobalt oxide, acetylene black, and polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3, then add N-methylpyrrolidone (NMP) as a solvent, prepare a slurry with a solid content of 75%, and stir evenly. The slurry is evenly coated on one surface of an aluminum foil with a thickness of 12μm, dried at 90°C, and cold pressed to obtain a positive electrode sheet with a positive electrode active material layer thickness of 100μm, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. Cut the positive electrode sheet into a specification of 74mm×867mm and weld the pole ears for standby use.
[0066] Negative electrode sheet: Mix the negative electrode active materials artificial graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 96:1:1.5:1.5, then add deionized water as a solvent, prepare a slurry with a solid content of 70%, and stir evenly. The slurry is evenly coated on one surface of a copper foil with a thickness of 8μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet with a single-sided negative electrode active material layer with a thickness of 150μm, and then repeat the above coating steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer. Cut the negative electrode sheet into a specification of 74mm×867mm and weld the pole ears for standby use.
[0067] Electrolyte: In a glove box filled with argon, LiPF6 as a lithium salt was dissolved in a solution containing: (I) diethyl carbonate (II) propyl propionate to prepare an electrolyte. Based on 100 parts by weight of the total mass of the electrolyte: the mass percentage of LiPF6 was 14%, the mass percentage of diethyl carbonate was 40%, and the mass percentage of propyl propionate was 45.4%. In addition, the parameters of substance A, substance B, and substance C in the electrolyte are shown in Table 1, and the parameters of substance D and fluorine-containing substance F are shown in Table 2.
[0068] Separator membrane: A polyethylene (PE) microporous membrane with a thickness of 8 μm was selected as the base membrane of the separator membrane. Boehmite (Dv50 of 1.5 μm, aspect ratio of 1:1) and polyvinylidene fluoride (molecular weight of 1.2 million) were mixed in a mass ratio of 3:2, and then N-methylpyrrolidone was added and stirred evenly to obtain a coating liquid, wherein the solid content of the coating liquid was 10%, and the coating liquid was applied to one surface of the base membrane of the separator membrane by dip coating to form a wet film, and the substrate with the wet film was immersed in a coagulation liquid containing deionized water and N-methylpyrrolidone for phase inversion, wherein the mass percentage of N-methylpyrrolidone in the coagulation liquid was 35%, and the temperature of the coating liquid and the coagulation liquid was 25°C. After being immersed in the coagulation liquid for 35 seconds, it was placed in an oven and dried at 50°C to obtain a porous membrane.
[0069] The pore size distribution coefficient of the porous membrane is adjusted by adjusting (the mass ratio of ceramics and polymers), the solid content of the coating solution, and the relative ratio of deionized water and N-methylpyrrolidone. The mass ratio of ceramics and polymers is 1:1~5:2, the time range of phase inversion is 2 seconds~9 seconds, and the ratio of deionized water and N-methylpyrrolidone meets the range of 0.6~1.2. The aspect ratio of inorganic particles is adjusted by screening with a filter screen with a specific aspect ratio shape to obtain inorganic particles with the required aspect ratio. The circularity of the pore size in the porous membrane cross section is adjusted by changing the stretching ratio of the porous membrane and the controlled temperature in the preparation process of the porous membrane. For example, the stretching ratio can be 2-4 times for transverse stretching and 2-6 times for longitudinal stretching, and the controlled temperature is 112℃-125℃. The pore size on the isolation membrane can be adjusted by selecting a base membrane raw material molecular weight of 80W~150W, a melting point of 133℃~140℃, and adjusting the mass ratio of ceramic and polymer on the porous membrane to 1:1~5:2 or adjusting the solid content of the coating liquid to 35%~50%. The parameters of the isolation membrane are shown in Table 3.
[0070] Assembly of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and obtain a lithium-ion battery after vacuum packaging, standing, formation, shaping, capacity testing and other processes.
[0071] Among them, the secondary batteries prepared by using the electrolytes 1-1 to 1-40 of the embodiments shown in Table 1, the separator 1-1 shown in Table 3, and the above-mentioned positive electrode sheet and negative electrode sheet are numbered as embodiments 1-1 to 1-40. The secondary batteries prepared by using the electrolytes 1-1 to 1-8 of the comparative examples shown in Table 1, the separator 1-1 shown in Table 3, and the above-mentioned positive electrode sheet and negative electrode sheet are numbered as comparative examples 1-1 to 1-5. Based on the parameters of the electrolyte 1-1, the secondary batteries prepared by adding or adjusting various substances according to the parameters shown in Table 2 and the separator 1-1 shown in Table 3 and the above-mentioned positive electrode sheet and negative electrode sheet are numbered as embodiments 2-1 to 2-24. Based on the parameters of the electrolyte 1-1, the secondary batteries prepared by using the separator shown in Table 3 and the above-mentioned positive electrode sheet and negative electrode sheet are numbered as embodiments 3-1 to 3-16.
[0072] The test method is as follows:
[0073] (1) Floating charge performance test:
[0074] Place the lithium-ion battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge with a constant current of 1C to a voltage of 4.2V, charge with a constant voltage to a current of 0.05C, and then discharge with a constant current of 1C to a voltage of 2.8V. Record the discharge capacity as the initial capacity of the lithium-ion battery. Then charge with a constant current of 0.5C to a voltage of 4.2V, charge with a constant voltage to a current of 0.05C, and use a micrometer to test and record the thickness of the battery as the initial thickness. Transfer the test lithium-ion battery to a 45°C constant temperature box, and then charge at a constant voltage of 4.2V for 60 days. After 60 days, transfer the battery to a 25°C constant temperature box, let it stand for 60 minutes, and discharge with a constant current of 1C to a voltage of 2.8V. Record the discharge capacity as the discharge capacity of the lithium-ion battery after storage. Then charge with 1C constant current to the voltage of 4.2V, charge with constant voltage to the current of 0.05C, and then discharge with 1C constant current to 2.8V. Record the discharge capacity as the recoverable capacity of the lithium-ion battery, and measure the thickness of the lithium-ion battery as the thickness after floating charge.
[0075] Float charge thickness expansion rate = (thickness after float charge - initial thickness) / initial thickness × 100%
[0076] Floating charge capacity retention rate = (initial discharge capacity - recoverable capacity) / initial discharge capacity × 100%.
[0077] (2) -15℃ 1C rate discharge test
[0078] At 25°C, the formed lithium-ion battery was charged to 4.45V at a constant current of 0.2C, then charged at a constant voltage until the current was less than or equal to 0.05C, then left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.2C. The discharge capacity of the lithium-ion battery at 25°C and 0.2C was obtained.
[0079] At 25°C, the lithium-ion battery was charged at a constant current of 0.2C to 4.45V, and then charged at a constant voltage to a current less than or equal to 0.05C; the battery cell was then placed in a -15°C environment, left to stand for 60 minutes, and then discharged at a constant current of 1C to 3.0V. The -15°C 1C rate discharge capacity of the lithium-ion battery was obtained by testing.
[0080] Lithium-ion secondary battery -15℃ 1C rate discharge capacity retention rate (%) = -15℃ 1C rate discharge capacity / 25℃ 0.2C rate discharge capacity × 100%.
[0081] (3) Acupuncture performance test
[0082] The battery was charged at 0.4C constant current to 4.2V, and then switched to constant voltage charging until the current was less than 0.05C and reached 100% SOC, i.e. the battery was fully charged. Before the test, the battery was left to stand for 30 minutes, fixed in the puncture test cabinet, and the temperature sensing wire and voltage wire were attached to the positive and negative poles. A 5mm diameter tungsten steel needle was used to penetrate the battery at the geometric center at a speed of 25±5mm / s, and the experimental phenomenon was observed. Each embodiment has 5 parallel samples, and those that do not catch fire are considered to have passed.
[0083] (4) Capacity storage test after 10 days storage at 45°C
[0084] At 25°C, the lithium-ion battery was charged at a constant current of 1C to a voltage of 4.45V, and then charged at a constant voltage of 4.45V to a current of 0.05C, and the initial capacity of the tested lithium-ion battery was C0; the lithium-ion battery was then placed in a constant temperature box at 45°C and stored for 10 days, and the 1C discharge capacity of the tested lithium-ion battery was C1, and then the lithium-ion battery was charged and discharged at a rate of 1C for 300 cycles at room temperature, and the 1C discharge capacity was recorded as C2.
[0085] The capacity retention rate (%) of lithium-ion batteries after 300 cycles of storage at 45°C for 10 days = (C1 / C0) × 100%;
[0086] The capacity recovery rate (%) of a lithium-ion battery after 300 cycles stored at 45°C for 10 days = (C2 / C0) × 100%.
[0087] (5) Isolation film elongation test
[0088] A special sample cutter is used to take 5 samples with a length*width of 100*15mm along a specific direction of the diaphragm for testing. The test speed is 50mm / min, the gauge length is 40mm, the force when the diaphragm breaks is recorded as the tensile force F1, the extension displacement of the diaphragm when it breaks is recorded as the tensile displacement L1, the cross-sectional area of the sample is S, and the original length of the sample is L0.
[0089] Elongation: Use a special sample cutter to take 5 samples with a length*width of 100*15mm along the TD and MD directions of the diaphragm for testing, with a test speed of 50mm / min and a gauge length of 40mm. When the diaphragm breaks, read the elongation test results in the MD and TD directions, and calculate the difference between the two accordingly.
[0090] (6) Side compression test of lithium-ion secondary batteries
[0091] At 25°C, the battery was charged to 4.4V at a constant current rate of 0.5C, and then charged to 0.05C at a constant voltage. The UL1642 test standard was adopted, and the side extrusion force was 13kN. The lithium-ion secondary battery was subjected to a side extrusion test, and 20 lithium-ion secondary batteries were tested in each group. The pass rate of the side extrusion test of the lithium-ion secondary battery was calculated.
[0092] (7) Test of thickness variation of porous membrane in width direction
[0093] Use a special cutter to randomly select five locations within 30mm from the end of the width direction of the diaphragm to cut out test pieces of TD 10mm×MD 50mm. Use the cryo-CP method to make cross-sectional samples of the test pieces, and then use SEM to observe the cross-section of each test piece to measure the thickness of the porous layer. During the process, a small amount of metal particles are vapor-deposited to prevent charging caused by the electron beam. The boundary line between the polyolefin microporous membrane and the porous layer is defined by the area where inorganic particles exist. Three samples are measured at each measurement position, and the average value of a total of 15 thicknesses is taken as the average thickness of the porous layer. The difference between the minimum values is defined as the thickness change of the porous layer in the width direction. Measuring device: field emission scanning electron microscope (FE-SEM) S-4800, cross-sectional polisher (CP) SM-9010, measurement conditions: acceleration voltage 1.0kV.
[0094] The lithium ion secondary batteries prepared in the above embodiments and comparative examples were tested for performance using the above method. The test results are shown in Tables 1, 2 and 3 below.
[0095] Table 1
[0096]
[0097] *In the above table, the abbreviations are as follows: PST: 1-propylene-1,3-sultone, TPP: tripropynyl phosphate, TMB: trimethyl borate, VC: vinylene carbonate, DMS: dimethyl sulfone, a: When the total mass of the electrolyte is regarded as 100 parts, a means that the mass of substance A accounts for a part of the 100 parts (i.e., the total mass of the electrolyte). b: When the total mass of the electrolyte is regarded as 100 parts, b means that the mass of substance B accounts for b parts of the 100 parts (i.e., the total mass of the electrolyte). c: means that the mass of substance C accounts for c parts of the 100 parts (i.e., the total mass of the electrolyte).
[0098] Table 2
[0099]
[0100] *In the above table, the abbreviations are as follows: c: the total mass of the electrolyte is regarded as 100 parts, c means that 1,3-dimethylimidazole dimethyl phosphate accounts for c parts in the 100 parts (i.e., the total mass of the electrolyte), d: the total mass of the electrolyte is regarded as 100 parts, d means that 1-propyl phosphoric acid cyclic anhydride accounts for d parts in the 100 parts (i.e., the total mass of the electrolyte), f: the total mass of the electrolyte is regarded as 100 parts, f means that the fluorine-containing substance F accounts for f parts in the 100 parts (i.e., the total mass of the electrolyte), the capacity retention rate / % is the capacity retention rate after storage at 45°C for 10 days, and the capacity recovery rate / % is the capacity recovery rate after storage at 45°C for 10 days.
[0101] Table 3
[0102]
[0103] Data analysis
[0104] Combined with Table 1, it can be seen that when the electrolyte contains substance A, substance B and substance C, due to the synergistic effect between substance A, substance B and substance C, the positive electrode material can be prompted to form a more uniform and dense solid electrolyte interface film on the interface of the positive electrode lithium cobalt oxide material, thereby improving the overall stability of the battery system. When the ratio of the mass percentage content a% of substance A to the mass percentage content b% of substance B is regulated to be within the range of 0.1≤b / a≤50, and the mass percentage content of substance A satisfies 0.2≤a≤2.5, compared with the control group without adding substance A, substance B and substance C, the floating charge capacity retention rate of the electrochemical device is significantly improved, the floating charge thickness expansion rate of the electrochemical device is reduced, and the high-rate discharge performance of the secondary battery at low temperature is improved.
[0105] In particular, when the mass percentage of substance A, the mass percentage of substance B and the ratio of the two in the above electrolyte are regulated to meet at least one of the following conditions: (1) 2≤b / a≤4; (2) 0.7≤a≤1.6; (3) 1.2≤b≤6.4, the range of the two substances can be limited to a more appropriate content, so that the floating capacity retention rate, floating thickness expansion rate and high-rate discharge performance of the electrochemical device can be more significantly improved. When the mass percentage of substance C in the above electrolyte and its sum with the mass percentage of substance A are regulated to meet 1.5≤c≤4, 2.2≤a+c≤4.7, the floating capacity retention rate, floating thickness expansion rate and high-rate discharge performance of the electrochemical device can be more significantly improved.
[0106] In particular, in combination with Table 2, it can be seen that when the electrolyte further contains substance D or fluorine-containing substance F, and the mass percentage content d% of substance D is regulated to satisfy 0.1≤d≤2, and the mass percentage content f% of fluorine-containing substance F satisfies 0.3≤f≤2, 0.7≤a+f≤2.7, substance D can improve the storage performance of the battery under high temperature conditions, the capacity retention rate at high temperature, and the capacity recovery rate at high temperature, improve the surface stability and structural compressive strength of the positive electrode material, thereby improving the test pass rate of the battery in the puncture test, and can also improve the storage performance of the battery at high temperature, and is also conducive to improving the charge and discharge recovery performance at high temperature. Fluorine-containing substance F can also further improve the stability of the battery and improve the storage performance of the battery at high temperature to a certain extent.
[0107] In particular, in combination with Table 3, it can be seen that the electrochemical device of the embodiment of the present application, on the basis of the aforementioned electrolyte, when the separator includes a porous membrane, and the pore size distribution coefficient of the porous membrane is regulated to meet the range of 1.5~4.5, the elongation of the separator in the transverse and longitudinal directions and the test pass rate of the side extrusion test of the secondary battery can be improved, and the high temperature performance can be improved to a certain extent. In particular, when the porous membrane includes inorganic particles and a binder, and the aspect ratio of the inorganic particles is regulated in the range of 1~5, the elongation of the separator in the transverse and longitudinal directions and the test pass rate of the side extrusion test of the secondary battery can be improved, and the high temperature performance can be improved to a certain extent. In particular, when the pores with a pore size of 0.0375μm in the separator account for 26%~38% of the total number of pores, and / or the pores with a pore size of 0.0325μm on the separator account for 42%~58% of the total number of pores, the elongation of the separator in the transverse and longitudinal directions and the test pass rate of the side extrusion test of the secondary battery can be improved, and the high temperature performance can be improved to a certain extent. In particular, when the circularity of the pore size in the cross section of the porous membrane in the separator is regulated within the range of 0.6 to 0.72, the elongation performance of the separator and the side extrusion test performance of the secondary battery can be improved, while the high temperature performance can be improved to a certain extent. In particular, when the difference in elongation between the MD direction and the TD direction of the porous membrane in the separator is in the range of 35% to 80% at 65°C, the secondary battery prepared has a higher test pass rate in the side extrusion test, while the high temperature performance is improved to a certain extent. In particular, when the thickness variation of the porous membrane in the separator in the width direction is in the range of 0.2μm to 0.7μm, the elongation of the separator in the transverse and longitudinal directions and the test pass rate of the side extrusion test of the secondary battery can be improved, while the high temperature performance can be improved to a certain extent.
[0108] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte comprises substance A, substance B and substance C; The substance A includes 1-propylene-1,3-sultone and / or tripropynyl phosphate; The substance B comprises vinylene carbonate and / or dimethyl sulfone; The substance C includes at least one of 1-dodecyl-3-methyl-imidazole dimethyl phosphate, 1-tetradecyl-3-methyl-imidazole dimethyl phosphate, 1-hexadecyl-3-methyl-imidazole dimethyl phosphate, 1-octadecyl-3-methyl-imidazole dimethyl phosphate, 1-dodecyl-3-methyl-imidazole diethyl phosphate or 1,3-dimethylimidazole dimethyl phosphate; Based on the total mass of the electrolyte, the mass percentage of substance A is a%, the mass percentage of substance B is b%, and the mass percentage of substance C is c%, 0.1≤b / a≤50, 0.2≤a≤2.5, 1.2≤b≤6.4, 1.5≤c≤4.
2. The electrolyte according to claim 1, characterized in that The electrolyte satisfies at least one of the following conditions: (1) 2≤b / a≤4; (2) 0.7≤a≤1.6。 3. The electrolyte according to claim 1 or 2, characterized in that 2.2≤a+c≤4.
7.
4. The electrolyte according to claim 1 or 2, characterized in that The electrolyte includes a substance D, and the substance D includes 1-propylphosphoric acid cyclic anhydride. Based on the total mass of the electrolyte, the mass percentage of the substance D is d%, 0.1≤d≤2, and 0.8≤a+d≤3.
4.
5. The electrolyte according to claim 1, characterized in that The electrolyte includes a fluorine-containing substance F, and the fluorine-containing substance F includes lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide. Based on the total mass of the electrolyte, the mass percentage of the fluorine-containing substance F is f%, 0.3≤f≤2, and 0.7≤a+f≤2.
7.
6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the content of lithium difluorophosphate in the fluorine-containing substance F is f1%, 0.3≤f1≤1.
5.
7. An electrochemical device comprising a separator and the electrolyte according to any one of claims 1 to 6.
8. The electrochemical device according to claim 7, characterized in that The isolation membrane comprises a porous membrane, and the pore size distribution coefficient of the porous membrane is 1.5-4.
5.
9. The electrochemical device according to claim 7, characterized in that: The isolation membrane comprises a porous membrane, the porous membrane comprises inorganic particles and a binder, and the aspect ratio of the inorganic particles is 1-5.
10. The electrochemical device according to claim 8, characterized in that The pore size of the isolation membrane satisfies at least one of the following conditions: (a) The pores with a pore size of 0.0375 μm on the isolation membrane account for 26% to 38% of the total number of pores; (b) The pores with a pore size of 0.0325 μm on the isolation membrane account for 42% to 58% of the total pores.
11. The electrochemical device according to any one of claims 8 to 9, characterized in that: The circularity of the pore diameter in the cross section of the porous membrane satisfies 0.6-0.
72.
12. The electrochemical device according to any one of claims 8 to 9, characterized in that: When the porous membrane is at 65° C., the difference between the elongation in the MD direction and the elongation in the TD direction is 35% to 80%.
13. The electrochemical device according to any one of claims 8 to 9, characterized in that: The thickness variation of the porous membrane in the width direction is 0.2 μm to 0.7 μm.
14. An electronic device, characterized in that: An electrochemical device comprising any one of claims 7 to 13.
Citation Information
Patent Citations
Nonaqueous electrolyte solution for secondary battery, and secondary battery provided with said solution
CN108475822A
Electrolyte
CN110165298A